Specific features of focused electron beam transport through a narrow metal tube at negative potential in the forevacuum pressure range. (April 2023) - Bakeev, I. Yu; Klimov, A.S.; Oks, E.M.; Zenin, A.A.
Abstract: We describe our investigations on the transport of a focused electron beam through a long and narrow metal tube, held at negative potential with respect to the vacuum chamber walls, in the elevated forevacuum pressure range. We have explored the effect of electron beam parameters and tube potential on beam transport. It is shown that the strength of this effect is connected to the initiation of a non-self-sustained glow discharge within the tube, as well as to the beam magnetic focusing parameters. We also show that increase in the fraction of electrons transported through the tube is conducive to uniformity of the distributions of the non-self-sustained discharge current and the discharge plasma density along the tube length. Highlights: Applying a negative potential to a metal tube affects the electron beam propagation in it. The potential effect is depends on the ignition of a non-self-sustained glow discharge. When the discharge in the tube is ignited, it improves beam transport through the tube. This effect ensures the discharge burns along the entire length of narrow tubes.